2017
DOI: 10.3390/robotics6030015
|View full text |Cite
|
Sign up to set email alerts
|

Compressed Voxel-Based Mapping Using Unsupervised Learning

Abstract: Abstract:In order to deal with the scaling problem of volumetric map representations, we propose spatially local methods for high-ratio compression of 3D maps, represented as truncated signed distance fields. We show that these compressed maps can be used as meaningful descriptors for selective decompression in scenarios relevant to robotic applications. As compression methods, we compare using PCA-derived low-dimensional bases to nonlinear auto-encoder networks. Selecting two application-oriented performance … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Brock et al (2016) also present successful results using variational autoencoders for reconstructing voxelized 3D data. Different configurations of encoding and decoding networks have also been proposed for achieving localization and for reconstructing and completing 3D shapes and environments (Dai et al, 2017; Elbaz et al, 2017; Guizilini and Ramos, 2017; Ricao Canelhas et al, 2017; Schönberger et al, 2018; Varley et al, 2017).…”
Section: Related Workmentioning
confidence: 99%
“…Brock et al (2016) also present successful results using variational autoencoders for reconstructing voxelized 3D data. Different configurations of encoding and decoding networks have also been proposed for achieving localization and for reconstructing and completing 3D shapes and environments (Dai et al, 2017; Elbaz et al, 2017; Guizilini and Ramos, 2017; Ricao Canelhas et al, 2017; Schönberger et al, 2018; Varley et al, 2017).…”
Section: Related Workmentioning
confidence: 99%
“…While SVOs only encode binary occupancy of voxels, the Truncated Signed Distance Field (TSDF) representation (Curless and Levoy, 1996) can be used to implicitly encode surfaces in a set of voxels. Recent work has shown that bricks of TSDF voxels can be compressed effectively by converting them into a lower dimensional latent space, using Principal Component Analysis (PCA) (Canelhas et al, 2017, Tang et al, 2018 or by training an encoder-decoder neural network (Tang et al, 2020).…”
Section: Efficient Visualization Of 4d Modelsmentioning
confidence: 99%
“…Instead, we build a local PCA-SDF shape representation, which represents each local shape as a linear combination of implicit volumetric prototypes, leading to finer details and order of magnitude faster inference than prior works. Similar eigenanalysis of SDF has been applied for either global shape representation [67] or geometry compression [68,69]. However, none of them develop their algorithms from our perspective of local shape priors, which is motivated from the assumption that local shapes at the voxel level share similarities.…”
Section: Related Workmentioning
confidence: 99%